Tanggung Jawab Sriwijaya Air Terhadap Penayangan Iklan Mengandung Janji Yang Belum Pasti Pada Promo SJ Travel Pass - Silmi Hanifa; Sylvana Murni Deborah Hutabarat (Jurnal Risalah Hukum, 2020)
Consumer protection is a guarantee that should be obtained by every consumer using goods or services. Law No. 8 of 1999 concerning Consumer Protection explains that the main factor that causes violations of consumer interests is due to the less of consumer awareness of their rights. This explains that consumers are faced with weak awareness and lack of understanding of their rights. Consumer rights and responsibilities of the company are related. Through this research will explain Sriwijaya Air's responsibility for the SJ Travel pass promo which has been detrimental to consumers because the advertisement display is not in accordance with reality. The method used in this study is normative juridical that based on existing legislation. The results of this study indicate that the Sriwijaya Air does not grant all consumer demands as a form of compensation, such as the extension of the SJ Travel Pass promo period. Consumer protection regulated in the UUPK can be said to be quite complete because it regulates the rights and obligations of consumers and business actors. The existence of consumer rights regulated in the UUPK strengthens the position of consumers to defend and fight for their rights. Keywords: Responsibility, Sriwijaya Air, Consumer Protection